Jamaican Cenozoic ichnology: review and prospectus. (25th November 2014) - Donovan, Stephen K.; Blissett, Donovan J.; Pickerill, Ron K.; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> Jamaica has the most diverse record of Cenozoic trace fossils of any of the Antillean islands, with over 100 ichnospecies divided among more than 50 ichnogenera. Trace fossils have been identified from both shallow‐ and deep‐water deposits in most major lithostratigraphic divisions, namely the Paleogene Richmond Formation (Wagwater Group), the mid‐Cenozoic White Limestone Group and the Neogene Coastal Group. Persistent ichnogenera in these palaeoenvironments include the burrows Palaeophycus Hall, Planolites Nicholson, Taenidium Heer and Thalassinoides Ehrenberg (deeper water), and the borings/microborings Entobia Bronn, Gastrochaenolites Leymerie and Oichnus Bromley (shallow water). Differences in diversity of ichnotaxa between formations can, in part, be due to differences in lithofacies and absolute water depth. This is recognized in the differences in deeper water lithofacies between the Richmond Formation (siliciclastic turbidites), White Limestone Group (chalks), Lower Coastal Group (submarine mass flow deposits) and Upper Coastal Group (deep fore reef). Intervals and lithofacies still awaiting detailed investigation include Pleistocene red beds and fore‐reef, Pliocene raised reef and shallow siliciclastic shelf, and most of the varied palaeoenvironments represented by the Eocene Yellow Limestone Group. Only crocodile coprolites (Eocene) are attributable to vertebrates; algal microborings apart, the only plant traces are Pleistocene root casts that await description. Copyright © 2014 John Wiley & Sons, Ltd.